The structure and growth characteristics of Oxalis tetraphylla Cav. (Oxalidaceae R. Br.) roots - A.I. Zhila; O.D. Timchenko (Інтродукція Рослин, 2016)
The new term “rachislike root” which is intended to be used for the modified adventitious napiform root of Oxalis tetraphylla Cav. is proposed. The adaptive flexibility and seasonal character of O. tetraphylla fibrous root system changing to the rachislike root system are considered. The initianion of adventitious roots takes place exclusively in the area of leathery scales from which the annual growth of bulbs begins. The formation of the so-called ephemerous root crop is the result of the inosculation of the lower part of stem-basal plate with the apical part of rachislike root. The occurrence of two types of adventitious roots – the rachislike (contractile, napiform, storage, in number 1–2) and threadlike (not contractile, feeding, thin, numerous) is established. It was shown, that in the process of growth the rachislike and threadlike roots which are co-originated and do not differ morphologically, undergo significant morphological transformations with, respectively, significant realignment of functions.